Egmundella producta G.O. Sars 1874 - Peter Schuchert (Zenodo, 2016)
Egmundella producta (G.O. Sars, 1874) Calycella producta G.O. Sars, 1874: 118, pl. 5 figs 6-8. ‒ Hincks, 1874a: 134. ‒ Verrill, 1879: 17. ‒ Storm, 1879: 26. ‒ Broch, 1907: 7. Manuscript accepted 0 3.02. 2016 DOI:10.5281/zenodo.155157 Lovenella producta . ‒ Segerstedt, 1889: 12. ‒ Jäderholm, 1909: 79. ‒ Kramp, 1935: 140, fig. 57E. ‒ Fraser, 1937: 96, pl. 19 fig. 102. ‒ Fraser, 1944: 175, pl. 31 fig 149. ‒ Schuchert, 2000: 423. ‒ Schuchert, 2001: 54, fig. 39. ‒ Calder, 2012: 22, fig. 21. Campanulina producta . ‒ Bonnevie, 1899: 73. ‒ Bonnevie, 1901:10. ‒ Broch, 1903: table. ‒ Stechow, 1922: 146. not Lovenella producta . ‒ Fraser, 1911: 44, pl. 3 figs 7-10. ‒ Fraser, 1914: 159, pl. 18 fig. 64. [in part Egmundella gracilis Stechow, 1921] ? Lovenella producta . ‒ Fraser, 1938: 40. ? not Campanulina producta . ‒ Leloup, 1940: 8, pl. 1 fig. 4. ? Egmundella grimaldii Leloup , 1940: 7, pl. 1 fig. 3. ? not Opercularella producta . ‒ Vervoort, 1966: 111, fig. 12a. ‒ Verwoort, 1985: 279. Material examined: Syntypes, UZMO B1378, Sars collection, as Calycella producta Norway, Bodø and Lofoten, 80-100 f (= 146-183); identified by G. O. Sars, numerous hydranths, relatively well preserved. MHNG-INVE-91796; Norway, North of Litlesotra Island, 60.4083°N 05.1167°W, 100 m depth, on tube of Sabella pavonia collected 22.04.2015; with 3 gonothecae; part of this material processed to permanent microslide preparations; DNA isolate 1097 made from a few hydranths, 16S sequence KU512889 DNA isolate 1098 made from a gonotheca content, 16S sequence identical to KU512889. MHNG-INVE-25136; Iceland, 64.842°N 24.217°W, 220 m depth, temperature 7.1°C; collection date 0 5.09.1990. ZMUC BIOFAR 100; Faroe Islands, 61.5878°N 6.2847°W, 283 m depth, temperature 6.8°C; collected 24.07.1987; without gonothecae. ZMUC BIOFAR 165; Faroe Islands, 62.1844°N 4.9667°W, 184 m depth, temperature 7.9°C, on hydroids; collected 07.05.1988; without gonothecae. ZMUC BIOFAR 517; Faroe Islands, 60.6039°N 11.6364°W, 1099 m depth, temperature 5.6°C; collected ...